2016
DOI: 10.1002/jor.23264
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal loading in the symptomatic and asymptomatic knees of middle‐aged osteoarthritis patients

Abstract: This study quantified the contributions by muscles, gravity, and inertia to the tibiofemoral compartment forces in the symptomatic (SYM) and asymptomatic (ASYM) limbs of varus mal-aligned medial knee osteoarthritis (OA) patients, and compared the results with healthy controls (CON). Muscle forces and tibiofemoral compartment loads were calculated using gait data from 39 OA patients and 15 controls aged 49 ± 7 years. Patients exhibited lower knee flexion angle, higher hip abduction, and knee adduction angles, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 52 publications
(119 reference statements)
3
30
0
Order By: Relevance
“…Although we do not know the precise mechanism by which upper partial fibulectomy improved HKA angle and reduced the overall peak KAM, we hypothesized that increased muscle activity of biceps femoris may be responsible. Compared with healthy controls, preoperative assessments showed that the KOA patients had significant lower muscle activity of biceps femoris for the affected (operated) side, which was in agreement with Sritharan et al Interestingly, the muscle activity increased immediately and was equivalent to controls by 6 months after surgery. Furthermore, we noted that after surgery the proximal fibula head was displaced superiorly in 10 cases and inferiorly in 19 cases.…”
Section: Discussionsupporting
confidence: 87%
“…Although we do not know the precise mechanism by which upper partial fibulectomy improved HKA angle and reduced the overall peak KAM, we hypothesized that increased muscle activity of biceps femoris may be responsible. Compared with healthy controls, preoperative assessments showed that the KOA patients had significant lower muscle activity of biceps femoris for the affected (operated) side, which was in agreement with Sritharan et al Interestingly, the muscle activity increased immediately and was equivalent to controls by 6 months after surgery. Furthermore, we noted that after surgery the proximal fibula head was displaced superiorly in 10 cases and inferiorly in 19 cases.…”
Section: Discussionsupporting
confidence: 87%
“…Thus a similar, albeit much more subtle, compensatory mechanism may occur in our OA patient cohort to facilitate functional improvements during gait, enabling them to walk at speeds comparable to controls despite advanced disease and symptoms of OA. In fact soleus and gastrocnemius muscle forces were lower in patients (Supplementary Table S2 and Sritharan et al) suggesting that kinematic adaptations in OA gait, currently understood to mitigate pain and improve knee‐joint stability, may also confer small but important advantages for lower‐limb muscle function. Further longitudinal research would help to determine if such functional adaptations do indeed develop with OA progression, and continue to change as these patients age and become less mobile.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported gait data for 39 medial knee OA patients and 15 healthy controls were used for this study (Table ). All gait experiments were performed at the Wolf Orthopaedic Biomechanics Laboratory, Fowler Kennedy Sport Medicine Clinic, University of Western Ontario.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations